Experimental study on heat exhaust coefficient of transversal smoke extraction system in tunnel under fire. (June 2015) - Yi, Liang; Wei, Ran; Peng, Jinzhi; Ni, Tianxiao; Xu, Zhisheng; Wu, Dexing
Graphical abstract: Highlights: Results of fire experiments with a model tunnel are provided. Effect of system configurations on heat exhaust coefficients is discussed. Heat exhaust coefficient of the smoke duct is measured in the range of 17–83%. Heat exhaust coefficient of the exhaust fans varies from 13% to 20%. Abstract: Heat exhaust coefficient of transversal smoke extraction system in tunnel under fire is studied by experimental means with a 1:10 model tunnel using Froude scaling. Heat exhaust coefficient is defined as the proportion of the heat exhausted by individual exhaust inlet, smoke duct and exhaust fans in total heat released by the fire in the tunnel, respectively. Results of a series of fire tests in a model tunnel are presented. Heat exhaust coefficient of single exhaust inlet and the smoke duct are strongly influenced by the configuration of the exhaust inlets. Heat exhaust coefficient of the exhaust fans varies in the range of 13–20% and is smaller than the heat exhaust coefficient of the smoke duct which varies from 17% to 83% and tends to be about 35% with the increase of the total area of the exhaust inlets. Activating small number of the exhaust inlets is beneficial for enhancing the heat exhaust coefficient of the smoke duct. The heat exhaust coefficient of the smoke duct and exhaust fans is high when the exhaust inlets are set close to the fire. Due to the cooling effect of the solid boundaries on the smoke while traveling in the tunnel and smoke duct, the heat exhaust coefficient of the exhaust fans in unilateral exhaust mode is slightly smaller than that in bilateral exhaust mode.